Ecological–health risk of antimony and arsenic in Centella asiatica, topsoils, and mangrove sediments: a case study of Peninsular Malaysia - Chee, Kong Yap; Wen, Siang Tan; Wan, Hee Cheng; Wan Mohd Syazwan; Wahid, Noor Azrizal; Krishnan, Kumar; Go, Rusea; Nulit, Rosimah; Ibrahim, Mohd. Hafiz; Mustafa, Muskhazli; Omar, Hishamuddin; Weiyun, Chew; et al. (Frontiers Media, 2022)
The current study assessed the ecological–health risks of potentially toxic arsenic (As) and antimony (Sb) in the vegetable Centella asiatica, topsoils, and mangrove sediments sampled from Peninsular Malaysia. The As concentrations ranged from 0.21 to 4.33, 0.18 to 1.83, and 1.32 to 20.8 mg/kg dry weight, for the leaves, stems, and roots of the vegetable, respectively. The ranges of Sb concentrations were 0.31–0.62, 0.12–0.35, and 0.64–1.61 mg/kg dry weight, for leaves, stems, and roots of the vegetable, respectively. The children’s target hazard quotient (THQ) values indicated no non-carcinogenic risks of As and Sb in both leaves and stems, although children’s THQ values were higher than those in adults. The calculated values of estimated weekly intake were lower than established provisional tolerable weekly intake of As and Sb for both children and adult consumers. The carcinogenic risk (CR) values of As for children’s intake of leaves and stems of vegetables showed more public concern than those of adults. The levels of Sb and As in the topsoils were generally higher (although not significantly) than those in the mangrove sediments, resulting in a higher geoaccumulation index, contamination factor and ecological risk, hazard index, THQ, and CR values. This indicated that the anthropogenic sources of Sb and As originated from the land-based activities before reaching the mangrove near the coast. The CR of As signifies a dire need for comprehensive ecological–health risks exposure studies, as dietary intake involves more than just vegetable consumption. Therefore, risk management for As and Sb in Malaysia is highly recommended. The present findings of the ecological–health risks of As and Sb based on 2010–2012 samples can be used as an important baseline for future reference and comparison.